ANALISIS KELAYAKAN USAHA PETERNAKAN ITIK PETELUR DI HARUM SELALU FARM KEC. GEGER KAB. MADIUN PROPINSI JAWA TIMUR - Imang Deni Irmawan; Ahsin Daroini; Rohmad Rohmad (Jurnal Ilmiah Fillia Cendekia, 2018)
Duck farming in Madiun Regency is not without problems. The common problems faced by duck breeders are the increasingly expensive cost of feed. The feed cost has a composition of more than 70 percent of the total production cost or maintenance cost. The research was conducted at "Harum Selalu Farm", Slambur Village, Geger District, Madiun Regency with survey method. The analysis method to find out the influence of the increase of feed price is used t-test (SPSS), to know the nonfinancial aspect is used descriptive method, while to explain the profit and feasibility of laying duck business used net income calculation (π), R / C, BEP, and Profitability. The conclusion is: (1) There is influence of feed raw material price to egg production; (2) Business feasibility analysis from non financial aspect is considered feasible. (3) The feasibility analysis of business from the financial aspect is considered feasible. This is proven by B / C Ratios of Harum Selalu Farm (1.011> 1), which means that the livestock business is feasible, the break even point of egg production to 43.930.5 kg (Rp 528.396.054, -), the value of R / C that is (1.22)> 1 business is said to be profitable so it is feasible to be gained with a profit of 21.51% (relatively low).